1999
DOI: 10.1161/01.cir.100.4.346
|View full text |Cite
|
Sign up to set email alerts
|

Effect of β-Blockers on Free Radical–Induced Cardiac Contractile Dysfunction

Abstract: OH. radicals induce an impairment of contraction and relaxation and an attenuation of the force-frequency relationship in human myocardium accompanied by an inhibition of SERCA. Carvedilol and BM-910228 partly prevented OH.-induced contractile dysfunction. These observations could explain the improvement of ejection fraction in heart failure trials with carvedilol without a restoration of beta-adrenergic receptor density.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
76
0
2

Year Published

2000
2000
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(83 citation statements)
references
References 38 publications
5
76
0
2
Order By: Relevance
“…17 Carvedilol prevented hydroxyl radical-induced cardiac contractile dysfunction in human myocardial tissue, but metoprolol did not. 18 These results suggest the possible importance of the use of carvedilol. Third, a recent study has revealed that carvedilol inhibits ROS generation by leukocytes.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…17 Carvedilol prevented hydroxyl radical-induced cardiac contractile dysfunction in human myocardial tissue, but metoprolol did not. 18 These results suggest the possible importance of the use of carvedilol. Third, a recent study has revealed that carvedilol inhibits ROS generation by leukocytes.…”
Section: Discussionmentioning
confidence: 92%
“…Carvedilol inhibits Fe 2ϩ -initiated lipid peroxidation and partially prevents hydroxyl radical-induced cardiac contractile dysfunction. 17,18 Carvedilol may reduce the oxidative stress level in the human failing myocardium via such various mechanisms. This study therefore was designed to determine whether carvedilol reduces the levels of HNE-modified protein in myocardia of patients with DCM.…”
mentioning
confidence: 99%
“…This observation is in close agreement with previous reports. [1][2][3]7,8,23 In rabbit myocardium, hydroxyl radical exposure leads to a degradation of TnT, associated with an increased calcium sensitivity of the myofilaments. However, inhibition of the calcium-dependent protease calpain I abolishes this TnT degradation and preserves calcium sensitivity, but it does not diminish acute diastolic dysfunction after hydroxyl radical exposure significantly.…”
Section: Discussionmentioning
confidence: 99%
“…Oxygen free radicals occurring during reperfusion after ischemia are thought to be involved in the development of "stunned myocardium" and in the development and progression of heart failure are associated with increased oxidative stress. [3][4][5][6] Free radical-induced myocardial dysfunction is characterized on different biological levels: oxygen free radical-exposed myocardial tissue and single cells show a severe diastolic dysfunction, 1,2 and contracting intact cardiac trabeculae from rabbit 7 and human 8 develop a rigor-like contracture marked by a severe and in part reversible increase in diastolic force and a loss of developed force. However, the mechanisms whereby oxidative stress acts remain speculative.…”
mentioning
confidence: 99%
“…Apoptosis can be induced by DNA damage and p53 up-regulation [6] which is affected by oxidative stress. Oxidative stress due to reactive oxygen species (ROS) takes part in oxygen toxicity causing damage to cellular and subcellular organelles such as the cellular membrane [7,8] and mitochondria [9] or sarcoplasmic reticulum [10] in cardiac myocytes. This damage is mediated by the oxidation of proteins and lipids through the modification of genomic and cellular structures [11].…”
Section: Introductionmentioning
confidence: 99%